Fitrah in Islam and Ren Xing in Confucianism: its relation to Islamic and Confucian ethics - Mohd Nor, Nur Suriya (2017)
This paper seeks to discuss the concept of fitrah in Islam and its relation to Islamic Ethics. Islamic Ethics is defined as “good character.” The motive force in Islamic ethics is the notion that every human being is called to “command the good and forbid the evil” in all spheres of life. Muslims understand the role of Prophet Muhammad as endeavouring to facilitate this submission. In Islam, man is inherently good on what is termed as fitrah i.e. innate disposition. The doctrine of fitrah is essentially that all human beings are born onto some disposition towards monotheism, along with a disposition to good moral values. Human beings exhibit both good and evil actions which tell that the humans are capable of both good and evil. Interestingly, Mencius believed that people in Confucianism are basically born good. According to him, human nature (ren xing) is inherently good and since we draw the difference between right and wrong from our own mind, these ideas are innate. Thus, this paper aims to highlight similarities between fitrah in Islam and ren xing in Confucianism.